PENGEMBANGAN BAHAN AJAR DIGITAL “BELACANTIKA” MENGGUNAKAN ARTICULATE STORYLINE - Nurazizah, Selvy; Permana, Irvan; Handayani, Rukmini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Development of Digital Teaching Materials "BELACANTIKA" Using Articulate Storyline Fraction Material. This study aims to determine the development and feasibility of digital teaching materials "BELACANTIKA" using Articulate Storyline fraction material. This study uses an R&D (Research and Development) approach using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. The subjects of this study were students of class IV-A of Madrasah Ibtidaiyah Swasta Amaliyah Cibinong in the odd semester of the 2024/2025 academic year. In this study, the instruments used consisted of validation sheets from media experts, language experts, material experts, student response questionnaires, and teacher response questionnaires. The results of the media validation obtained a percentage of 96%, the results of the language validation obtained a percentage of 94%, and the results of the material validation obtained a percentage of 100% with an average overall validation percentage from the three experts of 96% with the criteria "Very Feasible". The results of the student response questionnaire obtained a percentage of 97%, and the results of the teacher response questionnaire obtained a percentage of 98% with the criteria of "Very Good". Thus, it can be concluded that the development of digital teaching material, "BELACANTIKA", using Articulate Storyline fraction material, is very feasible and interesting to use in learning.